Including Material Exposure and Part Attributes in the Manual Assembly Line Balancing Problem. Issue 12 (2016) - Bortolini, M.; Faccio, M.; Gamberi, M.; Pilati, F.
Abstract: Assembly line balancing problem (ALBP) purpose is to assign assembly tasks to workstations optimizing a certain objective function. Despite this problem has been studied for decades, few contributions consider material exposure and part characteristics in ALBP. Furthermore, these features have relevant and practical implications for ALBP in the industrial context. This research proposes an innovative optimization model distinguished by different objective functions to properly balance assembly lines considering the aforementioned features. The model is tested and validated with a real industrial case study. The results demonstrates the importance of including material exposure and the optimal material storage within the assembly station in the assembly line balancing problem due to a strong influence of these on picking time, and so on the total assembly time.